Self-Oriented Empathy and Compassion Fatigue: The Serial Mediation of Dispositional Mindfulness and Counselor’s Self-Efficacy - Zhang, Lin; Ren, Zhihong; Jiang, Guangrong; Hazer-Rau, Dilana; Zhao, Chunxiao; Shi, Congrong; Lai, Lizu; Yan, Yifei (Frontiers in Psychology, 2021)
This study aimed to explore the association between self-oriented empathy and compassion fatigue, and examine the potential mediating roles of dispositional mindfulness and the counselor’s self-efficacy. A total of 712 hotline psychological counselors were recruited from the Mental Health Service Platform at Central China Normal University, Ministry of Education, then were asked to complete the questionnaire measuring self-oriented empathy, compassion fatigue, dispositional mindfulness, and counselor's self-efficacy. Structural equation modeling was utilized to analyze the possible associations and explore potential mediations. In addition to reporting confidence intervals, we employed a new method named model-based constrained optimization procedure to test hypotheses of indirect effects. Results showed that self-oriented empathy was positively associated with compassion fatigue both on the burnout and secondary traumatic stress dimensions. Dispositional mindfulness and counselor’s self-efficacy independently and serially mediated the associations between self-oriented empathy and compassion fatigue. The implication of this study suggests that it is useful and necessary to add some training for increasing self-efficacy in mindfulness-based interventions in order to improve compassion fatigue.